Perancangan Sistem Informasi Penyewaan Bus Berbasis Web di Pt. Dzakki Buana Tour - Abdulfattah, Faiz; Diansyah, Risnal; Jahpal, Habib; Balqis Windra, Tamimah; Khusnul Khotimah, Anisa (Universitas Muhammadiyah Riau, 2025)
The development of information technology has had a significant impact on various sectors, including services, operational efficiency, and data management. Information technology enables business processes to be conducted more quickly, accurately, and in an integrated manner, while also reducing the risk of errors from manual record-keeping. PT Dzakki Buana Tour, a company providing tourist bus rental services based in Pekanbaru, still carries out its business processes manually using tools such as Word, Excel, and Spreadsheets. This often leads to data entry errors, scheduling conflicts, and delays in service. This study aims to analyze and design a web-based bus rental application for PT Dzakki Buana Tour. The result of this research is a system design that includes client data management, rental processing, departure scheduling, and bus and driver management. The system design is illustrated using UML modeling tools such as use case diagrams, activity diagrams, and class diagrams. This system is expected to improve the efficiency and accuracy of the bus rental operations at PT Dzakki Buana Tour.